Enhancement of biocellulose production in mixed medium culture - Kah, Weng Siew (2012)
In this research,the results for biocellulose production by Acetobacter xylinus in mixed culture medium were reported. Biocellulose production was determined by utilizing different feedstocks of single sugars and sugar mixtures which were applied according to certain glucose to fructose ratio.Data for pH changes and the biocellulose production from every medium culture were thoroughly analyzed.In this experiment,it was ensured that all the samples had the initial temperature and pH of 30ºC and pH 5.5 respectively. The temperature was kept constant throughout the whole experiment while the changed pH value was taken as final pH at the end of the experiment for every sample.The highest production using sugar mixtures of 1:9 glucose to fructose ratio was 1.57g/L.The final pH values recorded in the different sugar mixtures were in the range of 4.0–5.5.The lowest final pH of 4.56 was determined in the medium that contained a single carbon source of glucose, as most of the glucose was converted into gluconic acid and lead to lowest biocellulose production of 0.69g/l.In contrast, the highest pH value of 5.3 was determined in the medium that contained a single carbon source of fructose and lead to the higher biocellulose production of 0.9g/l.Analyzing profiles for final pH and biocellulose production for the medium with higher glucose concentration showed that the glucose was preferable to be converted to gluconic acid rather than biocellulose synthesize.Besides,it was also determined that biocellulose production rate in mixed culture medium was higher than in culture medium that only consist of a single carbon source and this had proved that the experiment of enhancing biocellulose production with mixed medium culture was applicable.Results reported in this study demonstrated that the production of biocellulose can be enhanced by using carbon sources mixture with a suitable ratio.This not only represented that biocellulose would be a renewable source of cellulose in the future,but also might lead to major improvements in production if proper supplements and control were utilized in the fermentation process.